Hematopoiesis: the making of an immune system - Fairchild, Paul J. (Henry Stewart Talks, 2020)
The properties and subsets of hematopoietic stem cells (HSCs), Long-term versus short-term repopulating HSCs, Anatomical sites of hematopoiesis: primitive versus definitive hematopoiesis, The importance of quiescence in maintaining the integrity of HSCs, Lineage commitment and the role of cross-antagonism, Alternative models of hematopoiesis